Russia and anti-Western regimes in the Middle East - Mark Norman Katz (Amsterdam Law Forum, 2012)
This article discusses how Moscow’s policy of cultivating anti-Western regimes in the Middle East can result in Russian firms obtaining trade and investment deals in these countries that they might not have gotten if they had had to compete for them with Western firms. But it also notes that the downfall of these anti-Western regimes in the Middle East—whether as a result of external intervention, internal opposition, or a combination of both—can lead to the loss of whatever advantages these Russian firms previously obtained.